Occupational health hazards of trichloroethylene among workers in relation to altered mRNA expression of cell cycle regulating genes (p53, p21, bax and bcl-2) and PPARA. (2015) - Varshney, Meenu; Chandra, Abhijit; Jain, Rajeev; Ahmad, Riaz; Bihari, Vipin; Chandran, C. Keshava; Mudiam, Mohana K.R.; Patnaik, Satykam; Goel, S.K.
Abstract: Trichloroethylene (TCE) is widely used as a metal degreaser in industrial processes. The present study reports on the effects of TCE exposure on workers employed in the lock industries. To ensure exposure of the workers to TCE, its toxic metabolites, trichloroacetic acid (TCA), dichloroacetic acid (DCA) and trichloroethanol (TCEOH) were detected in the plasma of the subjects through solid phase microextraction-gas chromatography-electron capture detection. TCA, DCA and TCEOH were detected in the range of 0.004–2.494 μg/mL, 0.01–3.612 μg/mL and 0.002–0.617 μg/mL, respectively. Quantitative reverse transcription polymerase chain reaction analysis revealed up-regulated expression of p53 (2.4-fold; p < 0.05), p21 (2-fold; p < 0.01), bax (2.9-fold; p < 0.01) mRNAs and down-regulated expression of bcl-2 (67%; p < 0.05) mRNAs, indicating DNA damaging potential of these metabolites. No effects were observed on the levels of p16 and c-myc mRNAs. Further, as TCA and DCA, the ligand of peroxisome proliferator activated receptor alpha (PPARA), are involved in the process of hepatocarcinogenesis in rodents, we examined expression of PPARA mRNA and let-7c miRNA in the workers. No statistically significant differences in expression of PPARA mRNA and let-7c miRNA in patients were observed as compared to values in controls. Dehydroepiandosterone sulfate (DHEAS) is a reported endogenous ligand of PPARA so its competitive role was also studied. We observed decreased levels of DHEAS hormone in the subjects. Hence, its involvement in mediation of the observed changes in the levels of various mRNAs analyzed in this study appears unlikely.